Investigation of a hydrophobically associating polymer’s temperature and salt resistance for fracturing fluid thickener - Mao, Jincheng; Xue, Jinxing; Zhang, Heng; Yang, Xiaojiang; Lin, Chong; Wang, Quanhang; Li, Chao; Liao, Zhengjie (Colloid and polymer science, 2022)
Polyacrylamide (HPAM) is commonly used as a thickener in water-based fracturing fluids due to its good solubility and thickening ability. However, drawbacks such as the formation of high temperature and high salinity in oil and gas production currently limit its use as a thickening agent for fracturing fluids. To solve this problem, a hydrophobic associating polymer, DSAM (acrylamide/2-acrylamido-2-methylpropanesulfonic acid/acrylic acid/hydrophobic monomer AMD-12), with a good temperature and salt resistance was synthesized via complex initiated polymerization. The molecular structure of the synthesized polymer DSAM was confirmed using IR and 1 H NMR. The water solubility, thickening properties, and salt resistance of DSAM polymers were investigated. The results showed that the DSAM polymer solution’s apparent viscosity initially decreased with the addition of NaCl. However, as the salt concentration further increased, the DSAM polymer solution’s polarity also increased, as well as the hydrophobic association between molecules, resulting in a denser hydrophobic association network structure and an increase in the apparent viscosity of the polymer solution. The viscoelasticity test revealed that as the salt concentration increased, the viscoelastic polymer solution increased after initially decreasing, which was consistent with previous salt tolerance test results. Additionally, it exhibited superior temperature resistance, shear tolerance, and shear recovery capabilities compared with conventional HPAM. Meanwhile, the DSAM polymer can be completely broken down in the industry-standard time without residue. The benefits of DSAM polymers include salt thickening, high-temperature resistance, and thorough gel breaking. Thus, it has huge potential as a thickening agent for temperature-tolerant and salt-resistant fracturing fluid.